Outcomes of thyroid operations in patients of different age groups - Çiftçi, Ali; Tiryaki, Çağrı (The European Research Journal, 2021)
Objectives: To determine the effects of age on preoperative findings and on outcomes of thyroid surgeries. Methods: In this retrospective study, we analyzed the demographics, surgical and pathological data, postoperative complications and biochemical results including calcium, phosphorus and parathyroid hormone (PTH) levels of patients who undertaken thyroid operations. Results: Totally 288 consecutive patients operated for thyroid diseases were included in the study. The patients were grouped regarding their ages as patients in the 3rd decade (n = 26), 4th decade (n = 60), 5th decade (n = 81), 6th decade (n = 77) and 7th decade (n = 44). There was not any significant difference between groups regarding the preoperative diagnoses (p = 0.09). With an advance in age, the presence of multiple nodules in preoperative period was increasing (p = 0.015). On postoperative period, the pathological diagnosis was malignant in 46 (15.9%) patients. There was not any significant difference between groups regarding the tumor type (p = 0.80). The most common tumor type was papillary carcinoma in all age groups. Postoperative complications were determined in 68 (23.6%) patients and there was not any significant difference regarding the presence of postoperative complications in all age groups (p = 0.26). Conclusions: In conclusion, there was not any significant difference regarding postoperative outcomes in patients operated for thyroid diseases who were in the different decades of their lives. We can suggest that, thyroid surgeries are as safe in elderly patients as in younger patients.